An Enhanced Content Based Image Retrieval System using Color Features - C.Vasanthanayaki, R.Malini, (International Journal of Engineering and Computer Science, 2013)
This paper was motivated by the desire to improve the effectiveness of retrieving images on the basis of color content by Color Averaging technique. In this paper, a combined set of methods based on color averaging technique is proposed to achieve higher retrieval efficiency and performance. Firstly, an average mean based technique with reduced feature size is proposed. Secondly, a feature extraction technique based on central tendency is proposed. The proposed CBIR techniques are tested on Wang image database and indexed image database. Results obtained are compared with the existing technique based on memory utilization and query execution time. The experimental results show that proposed technique gives the better performance in terms of higher precision and recall values with less computational complexity than the conventional techniques.